Al Ghazāli’s Thoughts on Islamic Education Curriculum - Barni, Mahyuddin; Mahdany, Diny (Dinamika Ilmu, 2017)
Al Ghazali lived in the Islamic golden age when all the fields of education flourished. There have been many studies of al-Ghazali's thoughts, yet, further and deeper examination from various perspective is needed to get objective and actual thoughts of Al-Ghazali. In al Ghazali’s time, there was no term of curriculum, however, the concept emerged as an accumulation of previous thoughts about the curriculum. The objective of this research is to study about al Ghazali's thoughts on the curriculum of Islamic education based on the series of curricula before al-Ghazali which eventually distinguish this study from others. This library research relies on written materials from the works of al Ghazali and others related to this topic.  The data were collected using documentary technique and analyzed using content analysis method. In conclusion, Al-Ghazali’s curriculum is similar to the concept of holistic education which is characterized by intellectual, emotional, physical, and spiritual developments. The curriculum also covers the dimension of development and it is beneficial for individual and society to make people closer to Allah SWT.